2014
DOI: 10.4329/wjr.v6.i9.636
|View full text |Cite
|
Sign up to set email alerts
|

Echography in brain imaging in intensive care unit: State of the art

Abstract: Transcranial sonography (TCS) is an ultrasound-based imaging technique, which allows the identification of several structures within the brain parenchyma. In the past it has been applied for bedside assessment of different intracranial pathologies in children. Presently, TCS is also used on adult patients to diagnose intracranial space occupying lesions of various origins, intracranial hemorrhage, hydrocephalus, midline shift and neurodegenerative movement disorders, in both acute and chronic clinical settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…A bedside monitoring method for follow-up during further neurocritical care after DC on the ICU is thus desirable. As shown recently, bedside SDT may have the potential to serve as an adjunct to CCT in the assessment of ventricular dimensions with a high correlation to the "gold standard" [10][11][12]19]. In the present study, serial quantitative measurements of all four ventricle dimensions in identical patients after DC via SDT were compared to CCT with intraclass correlation coefficients ranging between 0.977 and 0.997 for all three measurements over time.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A bedside monitoring method for follow-up during further neurocritical care after DC on the ICU is thus desirable. As shown recently, bedside SDT may have the potential to serve as an adjunct to CCT in the assessment of ventricular dimensions with a high correlation to the "gold standard" [10][11][12]19]. In the present study, serial quantitative measurements of all four ventricle dimensions in identical patients after DC via SDT were compared to CCT with intraclass correlation coefficients ranging between 0.977 and 0.997 for all three measurements over time.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, the sonographic duplex technique (SDT) has been suggested as an adjunct to CCT to diagnose and monitor TBI patients after DC [10][11][12]. The sonographic duplex technique has been introduced as a reliable bedside tool that is available in almost every ICU and is already being used by a number of centers to monitor DC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The value obtained with US is quite similar to that referred to in Schröder et al [36] which found that the left LVV in 67% of all cases was wider than the right LVV. The differences between LVV measurements obtained using US and CT could be because a craniectomy was performed to access the brain when acquiring US images, thus inducing changes in the intracranial anatomy and, therefore, bias in the measurements [14,15]. In addition, the LVV measurements obtained using US could change depending on the angle of the probe over the brain surface, thus allowing image collection but not corrections, as is possible with the CT technique [50].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike US, access to CT and magnetic resonance (MR) techniques in veterinary medicine is limited to point centres. Compared with conventional neuroimaging methods, such as CT and MR, US is operator-dependent and have the advantages of low costs, short investigation times and repeatability; in addition, it does not have any harmful biological effects [14][15][16][17]. It is particularly suitable for imaging soft tissue and blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…17 Direct visualization of the brain using ultrasound can be done as well to monitor for midline shift, hydrocephalus, and hemorrhage. 18 Measurement from flow velocity tracings and calculated values (eg, Lindegaard ratio) are useful to evaluate for cerebral artery vasospasm. 17,19 The TCD Pulsatility Index may provide a noninvasive estimation of ICP by acting as a measure of increased resistance in distal arterioles.…”
Section: Transcranial Dopplermentioning
confidence: 99%